Penggunaan Media Interaktif Youtube dan Quizizz Paper Mode Terhadap Minat Belajar Siswa Kelas IV SDN Lemahireng 05 Dalam Pembelajaran Pendidikan Pancasila - Chintya Pramugita; Bernadetta Dewi Listyaningrum; Rusita Okta Kusuma; Nur Indah Wahyuni (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Effective learning will be realized by paying attention to several factors, one of which is student learning interest and teacher creativity in providing teaching ideas. With this high learning motivation and creativity level, it will increase the success of learning objectives. This study aims to determine the effect of using interactive learning media Youtube and Quizizz on the learning interest of fourth grade students of Lemahireng 05 State Elementary School in learning Pancasila Education material on Indonesian Cultural Diversity. The method used in this research is Classroom Action Research which is carried out with 2 cycles using a qualitative approach. The results obtained in this study, showed an increase in student interest in learning. This is evidenced by the percentage of learning interest in cycle I of 59.64% in the medium category and increased in cycle II to 74.29% in the high category. So it can be concluded that the application of youtube interactive media and Quizizz paper mode can increase learning interest in fourth grade students of Lemahireng 05 State Elementary School.